HUMAN RESOURCES DEVELOPMENT AT PT. PLN PERSERO - Nita Kanya (Jurnal Ekonomi, 2022)
PT. PLN Persero Distribution of West Java and Banten serves the public for electricity providers, especially in the West Java and Banten areas. In the field of human resource management, according to the Decree of the Board of Directors of PT PLN Persero number 1504.K/DIR/2011, the measurement of contractual achievement of employee performance targets is the result of a compilation of the results of measuring employee performance achievement and employee self-development programs (PDP programs). The type of research used is descriptive and verification research. This research is descriptive because in this research it describes a description that aims to get an overview of the variables of Leadership, Organizational Climate, Talent Management, Human Resource Performance obtained through tabulated data. The test results show that Talent Management variable is an intervening variable. Leadership significantly influences Employee Performance through Talent Management.